2017
DOI: 10.1097/md.0000000000007556
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of optic disc and ganglion cell layer in diabetes mellitus type 2

Abstract: The purpose of this study was to compare the optic disc parameters, retinal nerve fiber (RNFL), and macular ganglion cell layers between patients with diabetes mellitus (DM) type 2 and healthy controls.In this cross-sectional study, 69 eyes of 69 diabetic patients without diabetic retinopathy and 47 eyes of 47 healthy controls were included. Optic disc parameters (i.e., rim area, disc area, cup to disc ratio, cup volume), RNFL, and macular ganglion cell-inner plexiform layers (GCL + IPL) thickness were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
(23 reference statements)
0
5
0
1
Order By: Relevance
“…In previous studies, no differences in rim area, disc area or cup to disc ratio between pediatric patients with T1D and control group [17] were found. Only significant differences in c/d ratio were noted in patients with type 2 diabetes (T2D) without DR as compared to the control group [18]. In the studies, more binocular RNFL thickness asymmetry in diabetic patients in relation to the controls without significant differences in RNFL thickness [17,18] was also noted.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, no differences in rim area, disc area or cup to disc ratio between pediatric patients with T1D and control group [17] were found. Only significant differences in c/d ratio were noted in patients with type 2 diabetes (T2D) without DR as compared to the control group [18]. In the studies, more binocular RNFL thickness asymmetry in diabetic patients in relation to the controls without significant differences in RNFL thickness [17,18] was also noted.…”
Section: Discussionmentioning
confidence: 99%
“…5 Comparison of measurements of corneal nerve (CN) fiber length (mm/mm 2 ) for participants with type 2 diabetes mellitus (T2DM), circles, those who are obese without diabetes, diamonds, and two groups of people without diabetes or obesity from previous publications [12,22] been fully elucidated to date. Some studies have shown multiple statistically significant relationships related to this issue [24,25], but other studies have not [26], or just partially [27]. The roles of altered metabolic control and subclinical ischemia are presumed etiological factors in retinal neurodegeneration and axonal damages in T2DM [28].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the reactive gliosis and neuronal apoptosis are hypothesized as n early DR processes, and these imply DR as a neurovascular complication [ 23 ]. These neural alterations were also detected anatomically by using spectral domain optical coherence topography (OCT) in many studies concluding a thinning in the inner retinal layer as a result of DM [ 24 , 25 ]. Van Dijk et al [ 26 ] reported that, in the eyes with minimal DR, there was a thinning in the retinal nerve fiber layer (RNFL), inner plexiform layer (IPL), and ganglion cell layer (GCL) of the pericentral zone of the macula, while in the peripheral zone of the macula, only the RNFL and IPL were thinner compared with normal eyes.…”
Section: Discussionmentioning
confidence: 99%